1986
DOI: 10.1007/bf00220220
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethyl alcohol on the electrooculogram and color vision

Abstract: Color vision tests and electrooculography (EOG) were performed in 6 male and 2 female healthy young trichromatic volunteers between 60 and 130 min after finishing consumption of ethyl alcohol leading to blood levels of approximately 0.07% to 0.16%. The average number of errors in the desaturated Panel D-15 arrangement test rose from 0.86 to 2.0; the average error score in the Farnsworth-Munsell 100-Hue test rose from 26 to 79. The axis of errors in both tests was clearly tritanopic and tetartanopic, pointing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…However, there are some studies on organic solvents that make a temporal assignment possible. Ethanol has been shown to cause acute dyschromatopsia of the blue-yellow type after ingestion (Russel et al 1980;Zrenner et al 1986). The color vision impairment of 20 workers exposed to styrene did not improve after a holiday of 1 month (Gobba et al 1991).…”
Section: Toxicity Of Solvents To the Visual Systemmentioning
confidence: 99%
“…However, there are some studies on organic solvents that make a temporal assignment possible. Ethanol has been shown to cause acute dyschromatopsia of the blue-yellow type after ingestion (Russel et al 1980;Zrenner et al 1986). The color vision impairment of 20 workers exposed to styrene did not improve after a holiday of 1 month (Gobba et al 1991).…”
Section: Toxicity Of Solvents To the Visual Systemmentioning
confidence: 99%
“…The OKR analysis indicated that acute ethanol exposure affected visual function in zebrafish embryos, consistent with the changes in color vision that are observed in humans after an acute exposure to alcohol. 34,35 Normal light-adapted visual function recovered when the animals were allowed to swim in an ethanol-free environment for several hours.…”
Section: Ethanol Affects Photoreceptor Differentiation and Visual Funmentioning
confidence: 99%
“…Broadwell et al [5] found reduced blue-yellow color vision after exposure to solvent mixtures. Zrenner et al [39] also con®rmed earlier ®ndings of reduced blueyellow vision after ethanol intake. In view of these references, we did not use the red-green color vision test as the optimal choice.…”
Section: Visual Systemmentioning
confidence: 81%